Theorizing Transnational Migration: A Framework for Understanding Asian Migration to Australia Post-1973 - Tin, Nguyen Ly Trong; Duong, Nam Tien (Journal of Posthumanism, 2025)
Global migration, intensified by globalization and policy shifts, has reshaped societies, with Asian migration to Australia post-1973 offering a compelling case for theoretical advancement. This study proposes the Transnational Migration Cycle, a novel framework integrating globalization, transnationalism, and the migration-development nexus to analyze the formation, development, and transnational impact of Asian migrant communities in Australia following the abolition of the White Australia Policy. Drawing on a case study of Vietnamese, Chinese, Indian, and Filipino migrants, the framework emphasizes redefined push-pull dynamics, identity fluidity, and network-driven mobility. Findings reveal how historical policy changes, remittances, diaspora networks, and dual citizenship enable Asian migrants to navigate structural constraints and contribute to development in both Australia and their countries of origin, while facing integration challenges. The study advances migration theory by offering a dynamic, cyclical model that transcends traditional frameworks, with implications for policies supporting transnational engagement and social cohesion.